Penerapan Project Based Learning pada Mata Pelajaran Informatika di Pondok Pesantren Sematera Thawalib Parabek untuk Meningkatkan Keaktifan Belajar Peserta Didik - Nadiatul Putri; Hari Antoni Musril; Yahdi Yahdi (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to apply the Project Based Learning (PjBL) learning model as an effort to increase student learning activity. Through the implementation of PjBL, this research aims to create a learning environment that stimulates active student participation. With a focus on Informatics subjects in class VII at the Sumatra Islamic Boarding School Thawalib Parabek. The main aim is to contribute to the development of learning methods that encourage students to be more involved and active in the learning process, while improving their understanding and practical skills. This research uses a qualitative approach by applying classroom action research methods. The data obtained from this research is explained descriptively. Data collection techniques involve several methods, including participant observation, interviews. Participatory observation is used to understand the dynamics of interaction between students and learning with the PjBL model. In-depth interviews were conducted with teachers and students to obtain their views regarding experiences and perceptions regarding the implementation of PjBL. Document analysis includes study of learning materials, project assignments, and notes related to PjBL implementation. It is hoped that the research results will provide a comprehensive picture of the impact of the PjBL learning model on student activity in learning Informatics. It is hoped that the data collected from various data collection techniques can provide in-depth and relevant insights regarding the role of PjBL in increasing student activity.